RETRACTED: Analytical review of driving axles with integrated traction electric motors for commercial vehicles - Alyabiev Alexey; Akinin Dmitriy; Kartashov Aleksandr; Grinin Valeriy; Pikalov Nikita (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001